A critical review on ramucirumab in the treatment of advanced urothelial cancer. (May 2018) - Vlachostergios, Panagiotis J; Lee, Aileen; Thomas, Charlene; Walsh, Ryan; Tagawa, Scott T
Advanced urothelial cancer (UC) is a lethal disease despite current advances in systemic therapy, including platinum chemotherapy combinations and immune checkpoint inhibition. Tumor angiogenesis is involved in UC growth and metastatic progression. Proangiogenic signaling through the VEGFR is a key process in UC with prognostic significance. Targeting of VEGFR2 with the monoclonal antibody ramucirumab has been tested in various different tumor types. In this review, we discuss the development of the drug in the context of its preclinical and clinical use with a focus on UC. Improvements in our ability to predict responses and resistance are key for maximizing its efficacy and selecting the most appropriate combinations with other active agents.